PENINGKATAN KECAKAPAN AKADEMIK (ACADEMIC SKILL) SISWA DALAM PENERAPAN PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY APPROACH) - Hanifaturrahmah, Adinda Hanifaturrahmah; ', Yennita; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated by the low student’s academic skills in SMA Muhammadiyah 1 Pekanbaru, one of the learning that can be applied to improve the academic skill is guided inquiry approach because it can elaborate scientific thinking dan creativity. This research had been done in SMA Muhammadiyah 1 Pekanbaru on October 2014 until January 2015 that purpose to know the enhancement of academic skill in guided inquiry approach. . The design of the research is Pre-experimental design form one group pretest-posttest with the subject is X4 class. Based of the results obtained that the academic skills have increased after the implementation of guided inquiry approach, it is identifying variabels, making hypotheses, planning and doing experiment, based of analyses each meeting have increased. In general the indicator academic skill is obtained normalized gain in the middle category, with the result is the implementation of guided inquiry approach is effective to increase student’s academic skill in class X SMA Muhammadiyah Pekanbaru Key Words : academic skills, inquiry